THE ROLE OF SPIRITUAL INTELLIGENCE FOR LEADERSHIP COMPETENCY IN GOVERNMENT COMPANY - Arie Arumwardhani (Jurnal Psikologi, 2006)
Every organization has its goal to gain effectiveness. On the other side, without any supportsfrom competence leader, the goal will not be gained. The raise of leader’s competence should besupported by good knowledge, good skill and tha charisma to achieve something. In theglobalization era, Indonesia must prepare everything especially in human resource aspects tocompete with other countries. The aim of this study is to know how far the role of spiritualintelligence to leadership competency to fulfill the organization vision and mission in PT. JasaMarga (Persero). The participants of this study is 75 employees in different educationalbackground from diplome to doctor. From each independent and dependent variable, the studydevelops some supporting component such as spiritual inteligence and leadership competency.The result shows that spiritual intelligence has negative role to leadership competency. Theother results are personality has an effect to technical and humanism skills, and the leadershipability has an effect to conceptual skill.Key words: leadership competency, spiritual intelligence